Mechanical behavior of all-lignocellulose composites—Comparing micro- and nanoscale fibers using strain field data and FEM updating. (October 2022) - Jungstedt, Erik; Oliaei, Erfan; Li, Lengwan; Östlund, Sören; Berglund, Lars A.
Graphical abstract: Highlights: Nanoscale fibril composite was compared with microscale wood fiber (WF) composite. Differences in mechanical properties and deformation mechanisms were studied. Oriented WF had superior eco-indicators but properties comparable to random MFLC. FEM updating predicted 4 independent elastic constants from a single orthotropic WF composite. Abstract: Hot-pressed, binder-free wood fiber (WF) composites can serve as load-bearing and eco-friendly materials, and the comparison of nanoscale fibril reinforcement with microscale wood fibers is of interest. We investigated property differences and interpreted deformation mechanisms with strain field measurements using digital image correlation combined with orthotropic, elastic–plastic finite element model updating predictions. Random-in-plane microfibrillated lignocellulose (MFLC) composites showed better mechanical properties than WF composites due to stronger strain-hardening from lower porosity and better interfibrillar adhesion, provided by the intrinsic lignin-hemicellulose binder. Axially oriented wood fiber composites (O-WF) achieved comparable mechanical properties to random MFLC, with lower values for eco-indicators. The FEM updating method could successfully determine all 4 independent elastic constants from one 45° off-axis experiment, although the plasticity model required two more experiments.